TEACHER'S STRATEGY IN IMPROVING STUDENT'S LEARNING MOTIVATION: Indonesia - Alfain Hadid Bagaskara; Tajudin Nur; Yayat Herdiana (STIT Pringsewu, 2022)
Abstract The existence of this study aims to respond to several strategies that must be used by a teacher to complete the learning process. Teacher strategy is a general approach to teaching that is applicable in various subject areas and is used to meet various learning objectives. Teachers must have an ideal teaching strategy in the classroom to suit conditions that are usually different at each level. The type of method used in this research is a literature study that presents previously published material, and reports new facts or analyzes and a literature review provides a summary of the best and most relevant publications. Based on the results of this study that in an effort to provide motivation, teachers can analyze the motives behind students who are lazy to learn and have decreased achievement in school. The teacher's strategy is very necessary in increasing students' learning motivation, with the implementation of this strategy it is expected that students can improve their learning achievement. Keywords: Teacher's Strategy, Student's Learning Motivation